2018
DOI: 10.1016/j.micres.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Designer probiotic Lactobacillus plantarum expressing oxalate decarboxylase developed using group II intron degrades intestinal oxalate in hyperoxaluric rats

Abstract: Increased intestinal absorption of oxalate causes hyperoxaluria, a major risk factor for kidney stone disease. Intestinal colonization of recombinant probiotic bacteria expressing oxalate-degrading gene (OxdC) is an effective therapeutic option for recurrent calcium oxalate (CaOx) stone disease. Therefore, we aimed to develop food-grade probiotic L. plantarum secreting OxdC using lactococcal group II intron, Ll.LtrB and evaluate its oxalate degradation ability in vivo. Male Wistar albino rats were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 65 publications
0
13
0
1
Order By: Relevance
“…Understanding the expression, gene regulation, structural organization, and catalytic mechanism of OxDC and related oxalate-degrading enzymes is expected to advance efforts to enhance fungal resistance in crop plants and to lower their oxalate concentration ( 30 , 31 ). Other potential applications are being explored in the areas of oxalate scale remediation ( 32 , 33 ), novel therapeutics for hyperoxaluria and kidney stones ( 34 , 35 ), and bioengineered probiotic gut bacteria ( 36 , 37 ). Efforts have also been made to modify the protein to improve its catalytic activity at normal pH ( 38 ).…”
mentioning
confidence: 99%
“…Understanding the expression, gene regulation, structural organization, and catalytic mechanism of OxDC and related oxalate-degrading enzymes is expected to advance efforts to enhance fungal resistance in crop plants and to lower their oxalate concentration ( 30 , 31 ). Other potential applications are being explored in the areas of oxalate scale remediation ( 32 , 33 ), novel therapeutics for hyperoxaluria and kidney stones ( 34 , 35 ), and bioengineered probiotic gut bacteria ( 36 , 37 ). Efforts have also been made to modify the protein to improve its catalytic activity at normal pH ( 38 ).…”
mentioning
confidence: 99%
“…However, this study did not explore the underlying mechanisms. Later, some studies found that L. plantarum recombined with the oxalate decarboxylase gene could also reduce urinary levels (Sasikumar et al, 2014;Paul et al, 2018). However, these artificial bacteria may not be safe for humans.…”
Section: Ec Numbermentioning
confidence: 99%
“…Было показано, что в группе крыс, которым вводились данные бактерии, отмечалось значительное снижение мочевой экскреции оксалатов, а также уровня креатинина и мочевой кислоты в сыворотке крови [39]. Сходные данные по способности L. plantarum разлагать оксалаты в кишечнике были получены и в других экспериментальных исследованиях [40][41][42].…”
Section: роль Lactobacillus и Bifidobacterium в развитии вторичной гиunclassified